Local impacts of natural resource booms and busts - Toews, G (2014)
This thesis consists of five stand-alone chapters empirically evaluating questions relating to the life cycle of natural resource extraction. We use three different data sets to shed light on the local impacts of natural resource booms and busts. In chapter 2 to 4 we use the household budget survey of Kazakhstan to explore the impacts of the oil boom on the local population. In the second chapter, we explore the distributional effects of the oil boom and show that average household income increased and income inequality decreased. In the third chapter we study how the increase in average income was perceived by the local population and find that households' satisfaction with income decreased. In the fourth chapter we study how the boom affected households' expenditure and show that the likelihood that households pay tuition fees for tertiary education increased. In chapter 5, we explore the long-term impacts of a negative labour demand shock following the coal mine closures in the UK. To do this we construct a new data set containing the location of all active coal mines since 1981 and link it to the UK census. We find that the dramatic lay off of miners since 1981 was associated with a persistent reduction in female labour force participation in the affected districts. In chapter 6, we study the determinants of drilling costs and their impact on the real price of oil using a new global data set on the number of exploration wells drilled and costs of drilling. To do this, we propose a structural model of the upstream sector in the oil and gas industry. The model allows us to decompose the variation in the reduced form errors of the estimated VAR into three structural shocks, and estimate the dynamic responses of the variables in the system to these shocks. We confirm that the upstream sector of the oil and gas industry is subject to increasing costs. But we do not find that the real oil price is permanently affected by shocks to costs of drilling.